Quantification of Sterol and Triterpenol Biomarkers in Sediments of the Cananéia-Iguape Estuarine-Lagoonal System (Brazil) by UHPLC-MS/MS - Giovana Anceski Bataglion; Hector Henrique Ferreira Koolen; Rolf Roland Weber; Marcos Nogueira Eberlin (International Journal of Analytical Chemistry)
Sterols and triterpenols present in sedimentary cores from 12 stations along the Cananéia-Iguape estuarine-lagoonal system were investigated by ultra-high performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS). Ten sterols and three triterpenols were identified and quantified, indicating both natural and anthropogenic sources. The relative distributions of sterol and triterpenol showed that the study area is submitted to organic matter (OM) from the Ribeira de Iguape River, seawater, surrounding vegetation, and plankton production. The contribution of these sources depends on the region of the estuarine-lagoonal system and the depth of sediment. Regarding anthropogenic sources, only the samples submitted to freshwater flow from the Ribeira de Iguape River presented concentration of coprostanol higher than the threshold value and diagnostic ratios, coprostanol/(coprostanol + cholestanol) and coprostanol/cholesterol, that indicate moderate contamination by domestic sewage in that area of the estuarine-lagoonal system. Therefore, the approach used herein identified the OM sources and its transport along the Cananéia-Iguape estuarine-lagoonal system (Brazil), which is a complex of lagoonal channels located in a United Nations Educational, Scientific and Cultural Organization (UNESCO) Biosphere Reserve.